Cerebral venous thrombosis in adult patients with acute lymphoblastic leukemia or lymphoblastic lymphoma during induction chemotherapy with l‐asparaginase: The GRAALL experience. Issue 11 (8th October 2015) - Couturier, Marie‐Anne; Huguet, Françoise; Chevallier, Patrice; Suarez, Felipe; Thomas, Xavier; Escoffre‐Barbe, Martine; Cacheux, Victoria; Pignon, Jean‐Michel; Bonmati, Caroline; Sanhes, Laurence; Bories, Pierre; Daguindau, Etienne; et al.
<x xml:space="preserve">Abstract</x> Central nervous system (CNS) thrombotic events are a well‐known complication of acute lymphoblastic leukemia (ALL) induction therapy, especially with treatments including l‐asparaginase (l‐ASP). Data on risk factors and clinical evolution is still lacking in adult patients. We report on the clinical evolution of 22 CNS venous thrombosis cases occurring in 708 adults treated for ALL or lymphoblastic lymphoma (LL) with the Group for Research on Adult Acute Lymphoblastic Leukemia (GRAALL)‐induction protocol, which included eight L‐ASP (6, 000 IU/m2) infusions. The prevalence of CNS thrombosis was 3.1%. CNS thrombosis occurred after a median of 18 days (range: 11–31) when patients had received a median of three l‐ASP injections (range: 2–7). Patients with CNS thrombosis exhibited a median antithrombin (AT) nadir of 47.5% (range: 36–67%) at Day 17 (range: D3–D28), and 95% of them exhibited AT levels lower than 60%. There were no evident increase in hereditary thrombotic risk factors prevalence, and thrombosis occurred despite heparin prophylaxis which was performed in 90% of patients. Acquired AT deficiency was frequently detected in patients with l‐ASP‐based therapy, and patients with CNS thrombosis received AT prophylaxis (45%) less frequently than patients without CNS thrombosis (83%), P = 0.0002). CNS thrombosis was lethal in 5% of patients, while 20% had persistent sequelae. One patient received all planned l‐ASP infusions without recurrence of CNS thrombotic whereas l‐ASP injections were discontinued in 20 patients during the management of thrombosis without a significant impact on overall survival (P = 0.4). Am. J. Hematol. 90:986–991, 2015. © 2015 Wiley Periodicals, Inc.